Phytochemical Screening and Thin Layer Chromatography Analysis of Ethanol Extract of Bangle Rhizome (Zingiberis cassumunar Roxb.) - Ananda Choirinisa Eka Putri; Perdana Priya Haresmita; Indra Yudhawan; Diyah Tri Utami; Alfian Syarifuddin (Universitas Muhammadiyah Kalimantan Timur, 2025)
Bangle rhizome (Zingiber cassumunar Roxb.) is a part of the plant that is widely used in traditional medicine because its diverse secondary metabolites have great potential in treating various diseases. The aim of this research is to identify the content of curcumin and active compounds found in bangle rhizome (Zingiber cassumunar Roxb.) qualitatively and quantitatively using Thin Layer Chromatography and UV-Vis Spectrophotometry methods. The maceration method was used to extract the bangle rhizome with 70% ethanol solvent, resulting in an extract yield of 7.92%. The results of the study from qualitative analysis using Thin Layer Chromatography (TLC) with 3 different mobile phases, namely chloroform: ethanol (95:5), chloroform: methanol: glacial acetic acid (94:5:1), and chloroform: n-hexane: methanol (1:1:0.1), indicate that the ethanol extract from the bangle rhizome positively contains polyphenolic compounds, terpenoids, and glycosides. Quantitative analysis of curcumin using UV-Vis Spectrophotometry at a wavelength of 437 nm resulted in a linear equation y = 0.026x + 0.1026 with an R² value of 0.9958 and r = 0.997898. The absorbance values from the 3 replicates of the bangle rhizome ethanol extract sample solution obtained in this study were 0.35 nm; 0.38 nm; 0.392 nm, indicating the presence of curcumin in all three replicates of the bangle rhizome ethanol extract solution. Based on the research results, it can be concluded that the ethanol extract of bangle rhizome (Zingiber cassumunar Roxb.) positively contains polyphenolic compounds, terpenoids, glycosides, and curcumin.